Effects of bionic blades inspired by the butterfly wing on the aerodynamic performance and noise of the axial flow fan used in air conditioner. (August 2022) - Tian, Chenye; Liu, Xiaomin; Wang, Jiahao; Xi, Guang
Abstract: The axial flow fan, as a key part of the outdoor unit of air conditioner, has an important impact on the performance of air conditioner. In order to reduce the power consumption and aerodynamic noise of the outdoor unit, the outer edge profile with a depression structure, inspired by the effective control of butterfly wings for airflow, is reconstructed and adopted in the design of bionic blades. The effects of bionic blades with four different depression depths on the aerodynamic performance of the outdoor unit are investigated numerically. It is found that when the depression depth is 1.9 mm, the aerodynamic performance of the outdoor unit is the best. For the axial flow fan with the optimal design blade, the numerical simulation and experimental test on the noise of the outdoor unit are carried out. Based on the experimental results, the shaft power of the outdoor unit is reduced by 1% and the noise is reduced by 1.3 dB when the bionic blade with the depression depth of 1.9 mm is adopted. Based on the numerical results, the flow characteristics of the axial flow fan with the bionic blades is analyzed and the noise reduction mechanism of the depression structure is revealed. The studied results show that the depression structure with proper depth at the outer edge of the blades effectively changed the development and trajectory of the tip leakage vortex, which has a positive influence on the aerodynamic performance improvement and noise reduction of the axial flow fan.